Truth and Power in the Perspective of the ἀλήθεια. An Inquiry Concerning the Ontological Foundations of Contemporary Biopolitics in Heidegger’s ‘Parmenides - Candiloro, Javier Hernán (2017)
The purpose of this article is to reconstruct the genealogy of truth and power presented by Heidegger in the 54th volume of his complete works. The historical forms of truth and power appear together and, while on one hand they make reference to the ἀλήϑεια as their common origin, on the other hand they manifest themselves as a calculating, technical and scientific domination of life. The objective is to show this genealogy as an (im)political resistance strategy as a “biopolitical hypothesis”. In order to do so, truth will be made explicit as a fundamental mechanism of power and, correlatively, the desconstruction of metaphysics as an ethical and politic task. Finally, this will show Heidegger’s philosophical proyect as an antecedent of today’s biopolitics’ discussion.